Spectral patterns of the phenology of vegetative and reproductive development of huizache trees (Acacia farnesiana (L.) Willd.). - Casiano Domínguez, Marcos; Paz Pellat, Fernando (REVISTA TERRA LATINOAMERICANA, 2018)
The BBCH scale is widely adopted throughout the world for the description of the growth stages of several economically important crops, but a detailed description of the stages of phenological growth in huizache (Acacia farnesiana (L.) Willd.) has never been developed or followed up with remote sensors. The main objective of this work was to analyze the spectral and temporal patterns of the vegetative and reproductive development phenology (flowering only) of the huizache (Acacia farnesiana (L.) Willd.). Temporary monitoring of 11 huizache trees located in the urban park “La presa de San Jose”, San Luis Potosí, Mexico was implemented. The spectral measurements were made in the red (660 nm) and near infrared (830 nm) segments that were the inputs for the standardized index of vegetation for flowering and foliage (IVFFn) proposed by Casiano and Paz, while phenological stages were obtained in the BBCH numerical scale. The phenological patterns were analyzed in the spaces IVFFn-Time, BBCH-Time and IVFFn-BBCH. In the f irst two spaces, the results showed a vertical line where the stages of rapid vegetative development without stages of flowering are located as the recurrent pattern. Vegetative development and flowering as simultaneous stages are exhibited in an inclined plane. In the IVFFn-BBCH space it was possible to establish a clear relation between the different phenological stages including flowering of huizache (Acacia farnesiana (L.) Willd.) and vegetation indices, which provide f ield evidence of the scope of the IVFF and its relationship with the phenological stages in the BBCH scale, which allow us to propose a scheme for the modeling of the phenological stages for A. farnesiana (L.) Willd. from spectral data.